Porcine Esophageal Submucosal Gland Culture Model Shows Capacity for Proliferation and DifferentiationSummary - Richard J. von Furstenberg; Joy Li; Christina Stolarchuk; Rachel Feder; Alexa Campbell; Leandi Kruger; Liara M. Gonzalez; Anthony T. Blikslager; Diana M. Cardona; Shannon J. McCall; Susan J. Henning; Katherine S. Garman (Cellular and Molecular Gastroenterology and Hepatology, 2017)
Background & Aims: Although cells comprising esophageal submucosal glands (ESMGs) represent a potential progenitor cell niche, new models are needed to understand their capacity to proliferate and differentiate. By histologic appearance, ESMGs have been associated with both overlying normal squamous epithelium and columnar epithelium. Our aim was toÂ assess ESMG proliferation and differentiation in a 3-dimensional culture model. Methods: We evaluated proliferation in human ESMGs from normal and diseased tissue by proliferating cell nuclear antigen immunohistochemistry. Next, we compared 5-ethynyl-2â²-deoxyuridine labeling in porcine ESMGs inÂ vivo before and after esophageal injury with a novel inÂ vitro porcine organoid ESMG model. Microarray analysis of ESMGs in culture was compared with squamous epithelium and fresh ESMGs. Results: Marked proliferation was observed in human ESMGs of diseased tissue. This activated ESMG state was recapitulated after esophageal injury in an inÂ vivo porcine model, ESMGs assumed a ductal appearance with increased proliferation compared with control. Isolated and cultured porcine ESMGs produced buds with actively cycling cells and passaged to form epidermal growth factorâdependent spheroids. These spheroids were highly proliferative and were passaged multiple times. Two phenotypes of spheroids were identified: solid squamous (P63+) and hollow/ductal (cytokeratin 7+). Microarray analysis showed spheroids to be distinct from parent ESMGs and enriched for columnar transcripts. Conclusions: Our results suggest that the activated ESMG state, seen in both human disease and our porcine model, may provide a source of cells to repopulate damaged epithelium in a normal manner (squamous) or abnormally (columnar epithelium). This culture model will allow the evaluation of factors that drive ESMGs in the regeneration of injured epithelium. The raw microarray data have been uploaded to the National Center for Biotechnology Information Gene Expression Omnibus (accession number: GSE100543). Keywords: Esophagus, Barrettâs Esophagus, 3D Culture, Acinar Ductal Metaplasia, Adult Stem Cell